2004
DOI: 10.1097/01.sap.0000095441.40759.1f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guided Minimally Invasive Breast Surgery (UMIBS)

Abstract: The last 30 years has seen a shift in surgical treatment of breast diseases to less invasive, more conservative treatment options. The mammotome equipment was originally introduced as a diagnostic tool, but advances in technology have extended its role to therapeutic procedures. The mammotome device (8-gauge) is inserted through a cosmetically placed 4-mm scar and breast tissue is resected sequentially using a suction facility without the need to remove the biopsy device. This is done under ultrasound guidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In comparison, introduction of the vacuum‐assisted mammotome biopsy device in the diagnosis and treatment of benign and early breast cancerous lesions has the advantages of minimal invasiveness, is carried out under local anesthesia and produces cosmetic results, with an incision as small as 4 mm being required and no implantation of drainage tubes. Iwagwu et al succeeded in treating gynecomastia and fibroadenoma using the mammotome technique and achieved considerable cost savings, excellent cosmesis and high patient satisfaction . Similar to the previous studies of Iwuagwu, treatment of gynecomastia with MAMIR demonstrated a significantly smaller postoperative scar size, shorter hospitalization and healing times, lower postoperative pain levels, and higher patient satisfaction.…”
Section: Discussionmentioning
confidence: 64%
“…In comparison, introduction of the vacuum‐assisted mammotome biopsy device in the diagnosis and treatment of benign and early breast cancerous lesions has the advantages of minimal invasiveness, is carried out under local anesthesia and produces cosmetic results, with an incision as small as 4 mm being required and no implantation of drainage tubes. Iwagwu et al succeeded in treating gynecomastia and fibroadenoma using the mammotome technique and achieved considerable cost savings, excellent cosmesis and high patient satisfaction . Similar to the previous studies of Iwuagwu, treatment of gynecomastia with MAMIR demonstrated a significantly smaller postoperative scar size, shorter hospitalization and healing times, lower postoperative pain levels, and higher patient satisfaction.…”
Section: Discussionmentioning
confidence: 64%
“…Excellent cosmesis, reduced analgesic requirement and excellent patient satisfaction rate were noted (10,12). In addition to our initial seven patients, a further eight patients have since undergone this procedure in our unit, with consistently high patient satisfaction rates and excellent patientreported cosmesis.…”
Section: Discussionmentioning
confidence: 99%
“…It requires a 4 mm or smaller incision, with consequent reduction in pain along with preservation of periareolar sensation and excellent cosmesis. It also reduces the possibility of necrosis to either skin flap or nipple (10).…”
mentioning
confidence: 99%
“…8 Further to our initial study, published in 2004, the procedure was performed without ultrasound guidance; nevertheless, we achieved equally excellent results and patient satisfaction. 9 Although a comparative study with open surgery would have been ideal, there were no details of open surgery available at our institution.…”
Section: Discussionmentioning
confidence: 99%